ANTICARDIOLIPIN ANTIBODIES IN EYE AND NON-EYE MANIFESTATIONS OF VASCULAR DISTURBANCES IN PATIENTS WITH BEHCET’S DISEASE - N A Ermakova; Z S Alekberova; E L Nassonov (Научно-практическая ревматология)
Aim: Determining of possible relations between the presence of anticardiolipin antibodies (АСА) and occlusional thrombotic manifestations of Behcet’s disease(BD) Material and methods: Results of АСА study in 31 pts with BD depending on eye and other forms of occlusion or vascular thrombosis. Results: Increased АСА titers were found in 16.6% of pts and all of them belonged to the group with thrombosis of other than eye localization. No АСА was found in pts with isolated occlusional processes in fundus of the eye, in pts with combined occlusions of retinal vessels and thromboses of other then eye localization and also in pts without occlusional and thrombotic processes. Median level of АСА IgG was the highest also in BD pts with other than eye thrombosis (20.0±10.8 GPL). In pts with isolated occlusion of retinal vessels and pts without occlusional processes the level of median АСА IgG values was reliably lower (correspondingly 9,4±4,2 GPL, p<0,01; 6,9±6,4 GPL, p<0.01). Median АСА IgM level was higher in pts with simultaneous occlusion of retinal vessels and vascular thrombosis of other than eye localization (11,4±6,4 GPL, p<0,01). The lowest median level oj АСА IgM was observed in pts with isolated occlusion of retinal vessels (6,5±33,9 MPL). but the differences between groups of pts in АСА IgM determination were not statistically reliable. Conclusion: The obtained data enable us to suppose that АСА do not play a significant role in the development of occlusion of retinal vessels during BD.